ASSESSMENT OF CURRENT PRE-DISCHARGE NEONATAL JAUNDICE SCREENING PRACTICES IN GOVERNMENTAL HOSPITALS OF WEST BANK - Barhoush, Abeer (An-Najah National University, 2024)
About (60%) of mature and (80%) of premature newborns experience jaundice in the first 7 days of life, and about (10%) of themstay jaundiced till one month. Pre-Hospital discharge jaundice screening for early detection of newborns who are at risk is essential. This is the first study to assess the current practice of pre-discharge neonatal jaundice screening in governmental hospitals inthe West Bank. A questionnaire-based quantitative study was conducted among all pediatrician doctors who work at 8 West bank governmental hospitals, between September 2022 and May 2023. A structured Self-administered questionnaire was administered to participants who obtained from Personnel Affairs in selected Palestinian governmental hospitals a month before the data acquisition. A full of 138 pediatrician doctors participated in this study, which showed a relative weakness in adherence to jaundice screening guidelinesand the results of pediatricians' practices regarding the screening of neonatal jaundice were relatively low. pediatricians doctors shows low adherence levels and inadequate practices regarding screening of neonatal jaundice pre-hospital discharge. Studies are needed in our country to evaluate the impact of this practice on infants with jaundice.
تقييم الممارسات الحالية لفحص اليرقان الوليدي قبل الخروج من المستشفيات الحكومية في الضفة الغربية